Enhancing Hard Skill and Soft Skill Learning by Implementing the MBKM Program - Zainab Ompu Jainah; Muhammad Riza; Riza Muhida; Yanuar Dwi Prastyo; Intan Nurina Seftiniara (Lembaga Sosial Rumah Indonesia, 2022)
Education has developed very rapidly marked by the increase in the quality of education and world knowledge. The Indonesian government is trying to improve the quality of education by issuing a policy of Merdeka Belajar Kampus Merdeka (MBKM). This study aims to describe the model for strengthening the role of lecturers and students to improve hard skills and soft skills through MBKM at Bandar Lampung University. This research is descriptive qualitative research. Data collection using observation and documentation techniques. The results showed that the presence of the MBKM activity was a grant of freedom to educational institutions to choose the system of authority needed to create independence from the bureaucracy. With this, it can improve students' hard skills and soft skills: 1) improving soft skills that are more able to appear to interact with communication both verbally and visually effectively based on context, 2) improve soft skills through the competence of the best graduates with integrity and work ethic good and able to adapt to the environment, 3) can analyze the turmoil that occurs in the world of work so that soft skills and hard skills can be further improved, 4) can create innovative and creative works, 5) improve skills in the fields occupied to produce a work competent.